Online Library Management App Madrasah Aliyah Negeri Binjai - Zahra Azura; Samsudin Samsudin; Ali Ikhwan (The IJICS (International Journal of Informatics and Computer Science), 2022)
Technological changes to date are growing increasingly rapidly in various fields of life both in the field of health, the field of government, especially in the field of education. The world of education can also undeniably have a rapid impact on the development of technology, one of which is the means of school learning, namely the library. The library provides a platform for every student and student to develop their knowledge insight with various types of books. The use of technology to make library applications is needed in schools. This library application is made web-based and online, in this application will also be made sms reminder so that students are not late in returning books. This will greatly facilitate and speed up the performance of library officers who previously still use ledger records. So with the system that researchers designed at the Madrasah Aliyah State Binjai library can make library officers work more effectively and efficiently